New diseases of asparagus a threat to New Zealands biosecurity - Cheah, L-H; Davis, R.D. (New Zealand Plant Protection, 2002)
Three diseases asparagus rust Phomopsis stem blight and asparagus anthracnose were detected for the first time during 2000 on asparagus in Australia These diseases especially asparagus rust are likely to spread to other states in Australia and New Zealand They are a threat to New Zealands biosecurity Early detection of the diseases and application of control measures are essential to prevent the diseases spreading and enable eradication